High resolution density pedestal measurements during edge localized modes by short-pulse reflectometry in the TCV tokamak. (2nd July 2021) - Molina Cabrera, P A; Labit, B; Coda, S; Porte, L
Abstract: This publication presents high spatio-temporal resolution (mm µ s −1 ) density profile measurements of the pedestal top during type I, III, and small edge localized mode (ELM) H-mode plasmas in the tokamak à configuration variable (TCV). These measurements were performed using a novel short-pulse reflectometer. Average inter-ELM density profiles are obtained via conditional averaging using the D α trace as ELM indicator. Changes to the pedestal density profile gradients prior to type-III ELMs reveal unique pedestal dynamics leading to the ELM crash which can provide important experimental data for validation of non-linear MHD ELM simulations. The small-ELM scenario is found to feature a ∼25–35 kHz quasi-coherent density fluctuation near the separatrix ρ ψ ∼ 0.993–1.05 not observed during a similar type-I ELM discharge. This oscillation is also found in low-field-side magnetic pick-up probes displaying a ballooning character and n = +1 toroidal mode number. This oscillation could help explain the markedly different pedestal dynamics observed in the small-ELM regime.